Continuous spike-and-wave activity during slow-wave sleep in patients with rett syndrome - S. L. Kulikova; I. V. Kozyreva; S. A. Likhachev; M. Yu. Bobylova (Русский журнал детской неврологии)
The article presents a description of a clinical case of a child 3 years 8 months old with Rett syndrome caused by the mutation of p.Val485fs in the MECP2 gene. According to electroencephalography data at the age of 1 year and 6 months, diffuse continued epileptiform activity in the form of high-amplitude (up to 300 μV) acute – slow wave complexes (continuous spike-waves during slow-wave sleep, CSWS) with an index of 90–100 % was revealed. At the control examination at the age of 2 years and 10 months diffuse epileptiform activity was replaced by multifocal activity with an index of up to 70–80 % at certain epochs, in general, not exceeding 50–60 %. During the entire observation period there were no epileptic seizures. It remains unknown whether the presence of CSWS at such an early age is a predictor of a more severe course of Rett syndrome – in our observation the girl did not acquire walking skills and a delay in psychic and speech development was evident already before the 12 month of life. more research is needed on the frequency of the CSWS phenomenon and its role in the development of clinical features in Rett syndrome.